Electrical characteristics of rocks in fractured and caved reservoirs. (30th October 2017) - Tang, Tianzhi; Lu, Tao; Zhang, Haining; Jiang, Liming; Liu, Tangyan; Meng, He; Wang, Feifei
Abstract: The conductive paths formed by fractures and cave in complex reservoirs differ from those formed by pores and throats in clastic rocks. In this paper, a new formation model based on fractured and caved reservoirs is established, and the electrical characteristics of rocks are analyzed with different pore structures using resistance law to understand their effects on rock resistivity. The ratio of fracture width to cave radius ( C e value) and fracture dip are employed to depict pore structure in this model. Our research shows that the electrical characteristics of rocks in fractured and caved reservoirs are strongly affected by pore structure and porous fluid distribution. Although the rock electrical properties associated with simple pore structure agree well with Archie formulae, the relationships between F and φ or between I and S w, in more complicated pore structures, are nonlinear in double logarithmic coordinates. The parameters in Archie formulae are not constant and they depend on porosity and fluid saturation. Our calculations suggest that the inclined fracture may lead to resistivity anisotropy in the formation. The bigger dip the inclining fracture has, the more anisotropy the formation resistivity has. All of these studies own practical sense for the evaluation of oil saturation using resistivity logging data.